Душенька: роман / Н. Аронова - Аронова Наталья (Радость жизни, 2011)
Экземпляры: Селтинская районная библиотека (аб) (20110329) / Инвентарный номер: 197659 / Цена: 116.50 / Авт.знак: А 84 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6